2016
DOI: 10.1177/1477153515599189
|View full text |Cite
|
Sign up to set email alerts
|

Perceived adequacy of illumination, spatial brightness, horizontal illuminance and mean room surface exitance in a small office

Abstract: This paper presents a pilot study that investigated the suitability of mean room surface exitance as a predictor of spatial brightness and perceived adequacy of illumination, then compared these results with how horizontal illuminance predicted both items under the same conditions. An experiment used 26 participants and a small office. It exposed participants to three levels of mean room surface exitance, each delivered with three different light distributions and across three different surface reflectances, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…72,137,[139][140][141][142][143][144][145][146] These studies tend to show that an increase of radiant power in the short-wavelength region enhances spatial brightness. There is on-going consideration regarding whether this is best characterised by the rod receptors or by some combination of the s-cone receptor and ipRGC, 146,147 and with the adequacy of horizontal illuminance as a measure for spatial brightness: 148 Any proposals need to consider practicality alongside precision.…”
Section: Comparing Approachesmentioning
confidence: 99%
“…72,137,[139][140][141][142][143][144][145][146] These studies tend to show that an increase of radiant power in the short-wavelength region enhances spatial brightness. There is on-going consideration regarding whether this is best characterised by the rod receptors or by some combination of the s-cone receptor and ipRGC, 146,147 and with the adequacy of horizontal illuminance as a measure for spatial brightness: 148 Any proposals need to consider practicality alongside precision.…”
Section: Comparing Approachesmentioning
confidence: 99%
“…The author's discussions with several lighting professionals arrived at a reasonable consensus that the three levels of task illuminance in the third column, which cover the range commonly employed by regulators for specifying illuminances to be provided for general indoor lighting practice, could be expected to correspond with the PBI levels indicated. Duff et al 19,20 have reported a series of experimental studies conducted in both a viewing cabinet and a small office that found a linear relationship between subjects' assessments of spatial brightness and ambient illumination over an MRSE range of 25-100 lm/m 2 , and this provides the basis for the scale of MRSE levels indicated in the fourth column. Only the PBI-2 to PBI-4 values fell within the range of the experimental conditions, and the PBI-5 and PBI-6 levels are identified by asterisks as they are extensions of the experimental findings determined by multiplying the PBI-4 value by the same increments as occur for the E task values.…”
Section: Lpd Simulationmentioning
confidence: 97%
“…He developed procedures for measurement and calculation; 9 he compared the accuracy of alternative prediction formulae 10 and he conducted experiments which involved subjects making subjective assessments of their surrounding environments. 11,12 The outcomes of these experiments are examined in the following section and are shown to be particularly relevant to this paper.…”
Section: Duff's Researchmentioning
confidence: 99%
“…The first experiment involved subjects making brightness assessments while looking into a laboratory lighting booth, 11 and for the second experiment, they were seated in a small office and they assessed both brightness and illumination adequacy. 12 A feature of these experiments was the consistency with which the experimental conditions were maintained. For both experiments, the same group of 26 subjects was presented with 27 viewing situations, nine at each of three sittings.…”
Section: Duff's Researchmentioning
confidence: 99%